If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = y Reorder the terms: 2 + 6x = y Solving 2 + 6x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6x = -2 + y Combine like terms: 2 + -2 = 0 0 + 6x = -2 + y 6x = -2 + y Divide each side by '6'. x = -0.3333333333 + 0.1666666667y Simplifying x = -0.3333333333 + 0.1666666667y
| 12n+44=-304 | | 53-2x=13-9x | | 6(1-36x)-20(4x-29)=-6 | | 9(-3)=2(9-13) | | 17(1-a)-26(a-8)=268 | | 6x-4=3x+4 | | 36=18x-12+6 | | 8x-6=4x+4 | | 7(6-38v)+27(11+13v)=-1 | | 10x+9=7x+6 | | y-x=-1 | | 5(x-3)+22=57 | | 2[3x+4(x-5)]-4x=12 | | 10-2q+5q= | | 2[3x+4(4x-5)]-4x=12 | | y=400x+200 | | 42n-23=6(12x-7) | | 173600=X+(X*1.12) | | 6x-6=9x+9 | | 4.93-9.2p=.66p | | 8y+11=-7y-19 | | 41-7x=2x+24 | | 5m-43=2m+80 | | 3x+6=x-8 | | 2x+8=4x+5 | | 6x^4-x^3=0 | | 7n-5=10n+13 | | y=x^4-6x^3+9x^2+4x-12 | | -6x=2y-10 | | 16+3x=8+32 | | 6y=5(y+11) | | 8-4x=6x-18 |